Raízes do surf: o desafio da educação ambiental para crianças no litoral do Salgado Paraense, Praia de Ajuruteua, Bragança - PA - REMIGI, Pablo (2018)
Work on Environmental Education help in Ajuruteua beach, located in the municipality of Bragança, east coast of the State of Pará, is part of the project "Surf Roots", the result of the selection of projects for public sponsorship of Banco da Amazônia in 2012 The main objective of this work, developed over a year, was to develop environmental education practices and policies with children living in a small community of fishermen on the Amazonian coast. Through the encouragement of Surfing and other activities, it was sought to involve the UFPA community and students in the socio-environmental issues of that region. Education is an ongoing process, so it is not possible to establish specific evaluation parameters, each case having its own particularities. However, from the analysis of the results obtained, we note the development of a series of practices consistent with the needs and objectives raised, allowing us to respond succinctly during the conclusions, some of the main issues raised by the project. Has such work really brought about changes in the behavior of this community? What are the main obstacles and achievements of this type of research? Questions that will undoubtedly be of fundamental importance for the approach to future work in this area of ​​knowledge.